(3YhGQa GdeYGQas - (3TgGH GdOjf CHh MaU YeQ Hf eMeO Hf YHO Gddg GdSgQhQOj GdTGaYj, GdSgQhQOj,J (B632 (3g` s ((3CMeO Hf eMeO GHf MSf Hf Ydi s)
(3ChdgG (B:s
(3GdMeO ddg GdYXje TCfg Gdbhj SdWGfg GdXGgQ GMSGfI GdHGgQ MLJg hHQgGfg GdeMJLH HGdLdGd hGdefaQ HGdceGd s
(3BNQgG (B:s
(3bO CMH Gddg adGfkG aCMHg ajLjHg LHQjd Ke jfGOj LHQjd aj GdSeGA Gf Gddg bO CMH adGfkG aCMHhg , ajLjHI Cgd GdSeGA , aHhVY dg GdbHhd aj GdCQV Ke cJGH YhGQa GdeYGQa s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3eJaQbGJs